Calculator for Substitution Method
Solve:
a
_{11}
x + a
_{12}
y = b
_{1}
a
_{21}
x + a
_{22}
y = b
_{2}
x +
y =
(eq.1)
x +
y =
(eq.2)
Solve the first equation for y:
(note that we could solve first for x as well)
y =
x +
(eq.3)
Plug-in the the right side of eq.3 into the eq.2
and simplify to obtain the first component of the solution vector.
x =
(eq.4)
Plug-in eq.4 to the eq.1 to obtain the second component of the solution vector.
y =
Table of Contents:
Definitions
Procedures
Incremental Calculator I
Incremental Calculator II
Incremental Calculator III
Graphical Calculator
Keyword Cycling Test Learning
Main Table of Contents